2023
DOI: 10.3847/1538-4357/acefcd
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Emission Modeling of GRB 221009A: Shedding Light on TeV Emission Origins in Long GRBs

Hebzibha Isravel,
Damien Bégué,
Asaf Pe’er

Abstract: Observations of long-duration gamma-ray bursts (GRBs) with TeV emission during their afterglow have been on the rise. Recently, GRB 221009A, the most energetic GRB ever observed, was detected by the Large High Altitude Air Shower Observatory experiment in the energy band 0.2–7 TeV. Here, we interpret its afterglow in the context of a hybrid model in which the TeV spectral component is explained by the proton-synchrotron process while the low-energy emission from optical to X-ray is due to synchrotron radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…However, the previously reported >10 TeV photons clearly cannot be explained by the SSC process (Huang et al 2022). Further investigation is needed to determine whether observable hadronic processes are present during the afterglow phase (e.g., Sahu et al 2022;Isravel et al 2023). 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, the previously reported >10 TeV photons clearly cannot be explained by the SSC process (Huang et al 2022). Further investigation is needed to determine whether observable hadronic processes are present during the afterglow phase (e.g., Sahu et al 2022;Isravel et al 2023). 3.…”
Section: Discussionmentioning
confidence: 99%
“…From the smoothness of the TeV light curve (LHAASO Collaboration 2023), one may conclude that it comes from the external shock. Wang et al (2023b) and Isravel et al (2023) modeled the whole multiband light curve from keV to TeV, and they all found both the hadronic and leptonic processes should have contributed to the multiband emission, while Ren et al (2023) suggested a structured jet that can explain the multiband emission. Previous studies have also investigated the optical depth of TeV photons in GRB 221009A.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout this work, the convention Q x = Q/10 x is adopted. It is also the first GRB with photons of energy extending up to ∼10 TeV (LHAASO Collaboration et al 2023a, indicating its potential ability of accelerating UHECRs (Alves Batista 2022; Zhang et al 2023aZhang et al , 2023bDas & Razzaque 2023;Isravel et al 2023;Mirabal 2023). Likely, only 1 of 10,000 randomly generated long bursts is as energetic as GRB 221009A, and the rate of GRBs as nearby and as energetic as GRB 221009A is 1 per 1000 yr (Burns et al 2023;Williams et al 2023).…”
Section: Introductionmentioning
confidence: 99%